Area handbook for the Republic of Tunisia - Reese, Howard C.; Systems Research Corporation; American University (Washington, D.C.) (Washington : The American University, 1970)
This book is an attempt to provide, in compact, convenient, balanced and objective form, an integrated exposition and analysis of the dominant social, political and economic aspects of the Tunisia society.
"DA pam 550-89."
"One of a series of handbooks prepared under the auspicies of Foreign Area Studies."
Includes bibliographical references: p. 381-401.
aia 04/05/2017
Ref
Keywords: Tunisia